Demonologia i magia ludowa w folklorze mieszkańców Nasielska - Lisiecki, Marcin (Humaniora. Czasopismo Internetowe, 2024)
The article presents the material from the field research I conducted in Nasielsk and its surrounding villages. From a reasonably rich collection of interviews, I have selected fragments that refer to the verbal folklore preserved in the memory of the inhabitants of Nasielsk. To more accurately extract and present oral legend, the article is divided into two parts. First, I deal with topics related to folk demonology and belief in the operation of ‘unclean forces’ among the inhabitants of the local community. On the other hand, the second part is devoted to narratives related to magic and ways to counteract it.